Komunikasi matematis siswa melalui model pembelajaran kooperatif tipe memeriksa berpasangan - Nur Rachmawati, Lelly; Muhammad, Ilham; Sugianto, Rahmad; Choirudin, Choirudin (Rafandha Press, 2023)
Mathematical communication is one of the abilities that needs to be improved considering the number of studies that still show low students' mathematical communication skills. The purpose of this study was to describe students' mathematical communication through a cooperative learning model of the type of checking in pairs. This type of research is descriptive research with a qualitative approach. The research subjects were 10 students of class VII. The research instrument was a test question sheet which contained material on a system of linear equations with one variable in the number of 2 questions. The research steps are preparation, implementation and drawing conclusions. Preparation was carried out by studying literature and compiling research instruments. Implementation, carried out by carrying out learning and collecting data. Conclusions are drawn based on analysis through the stages of reduction, presentation, and drawing conclusions. The research findings show that students are able to write down mathematical situations by writing down the known information and being asked questions. . Students are able to write down ideas well in determining the value of variable x in a given problem.